The Red Supergiant Progenitor of the Type II Supernova 2024abfl - Jingxiao Luo; Lifu Zhang; Bing-Qiu Chen; Qiyuan Cheng; Boyang Guo; Jiao Li; Yanjun Guo; Jianping Xiong; Xiangcun Meng; Xuefei Chen; Zhengwei Liu; Zhanwen Han (The Astrophysical Journal Letters)
Linkage between core-collapse supernovae and their progenitors is not fully understood and ongoing effort of searching and identifying the progenitors is needed. SN 2024abfl is a recent Type II supernova that exploded in the nearby star-bursting galaxy NGC 2146, which is also the host galaxy of SN 2018zd. From archival Hubble Space Telescope data, we have found a red source (m _F814W  ∼ 25) near the location (angular distance ≤0 $\mathop{.}\limits^{\unicode{x02033}}$ 2) of SN 2024abfl before its explosion. With F814W and F606W photometry, we found that the properties of this source matched a typical red supergiant (RSG) moderately reddened by interstellar dust at the distance of the host galaxy. We conclude that the SN 2024abfl had an RSG progenitor with initial mass of 9 –12 M _⊙ .